Assessing Flood Risk Dynamics in Southern Laos: A Comparative Analysis of HEC-RAS, Empirical and Physically Based Froude Number Models along the Xekaman River - Ketsana PHOMMAVONG; Jianguo YAN; Chikondi CHISENGA; Shoukat Ali SHAH (Chinese Journal of Urban and Environmental Studies)
Flooding, intensified by climate change, urbanization, and unsustainable land use, presents a significant danger to riverine communities, especially in Southeast Asia. This study analyzes flood dynamics along the Xekaman River in Attapeu Province, Laos, employing the empirical Froude number (EFR) and physically based Froude number (PBF) models, in conjunction with Hydrologic Engineering Center’s River Analysis System (HEC-RAS), to evaluate river flow and flood risk over 72[Formula: see text]h in 2022. The EFR model achieves a peak flow velocity of 15[Formula: see text]m/s at 12[Formula: see text]h, whereas the PBF model reaches 10.96[Formula: see text]m/s. At 72[Formula: see text]h, peak velocities increase to 75 and 109.97[Formula: see text]m/s, respectively, demonstrating substantial disparities in flow conditions. The EFR model offers a wider distribution of flood risk, while the PBF model delivers a more accurate representation of extreme flood events. HEC-RAS improves analysis by providing comprehensive floodplain delineation, variations in water depth, and distribution of flow velocity, thereby enhancing the spatial precision of flood risk evaluations. These findings highlight the necessity of incorporating various modeling methods to enhance flood risk assessments and monitoring, and optimize mitigation initiatives in flood-prone areas.